Radiotherapy for patients with unresectable advanced hepatocellular carcinoma with invasion to intrahepatic large vessels: Efficacy and outcomes. Issue 2 (February 2014) - Tanaka, Yoshiaki; Nakazawa, Takahide; Komori, Shouko; Hidaka, Hisashi; Okuwaki, Yusuke; Takada, Juichi; Watanabe, Masaaki; Shibuya, Akitaka; Minamino, Tsutomu; Yamamoto, Hajime; Kokubu, Shigehiro; Hayakawa, Kazushige; et al.
Abstract Background and Aim To examine the efficacy and outcomes of radiotherapy (RT) in patients who have hepatocellular carcinoma with invasion to intrahepatic large vessels (IHLVs). Methods Sixty‐seven patients who had advanced hepatocellular carcinoma with invasion to IHLVs received three‐dimensional conformal RT. IHLV invasion was associated with portal venous tumor thrombosis in 40 patients, tumor thrombosis involving the hepatic vein in 17, and both findings in 10. A daily radiation dose of 1.8–2 Gy was administered using 6 or 10 MV X‐rays to deliver a total dose of 30–56 Gy. Results The overall objective response rate (complete response plus partial response) was 45% (n = 30). The median survival time was 13.7 months in the responder group and 5.9 months in the nonresponder group. An objective response was observed in 28 (56%) of 50 patients with Child‐Pugh (C‐P) class A and in 2 (12%) of 17 patients with C‐P class B. Hepatic function of C‐P class A was an independent factor for both RT responder and overall survival on Cox regression analysis (hazard ratio = 9.5, 95% confidence interval = 1.97–46.2, P = 0.005; and hazard ratio = 0.39, 95% confidence interval = 0.2–0.77, P = 0.007, respectively). Conclusion RT is an effective treatment option without serious adverse events. RT should be considered for the patients with better hepatic function who have invasion to IHLVs.